Estrategias didácticas activas para fomentar el pensamiento crítico reflexivo en los estudiantes del sexto semestre la Carrera de PCEI periodo abril – septiembre 2022 - León Galarza, Damaris Nohelia (2022)
Reflective critical thinking has become essential for all human beings due to its great utility in solving problems in education and in everyday life. The increase in the development of this thought allows to provide a good training to the students to make them autonomous, innovative and critical. The main objective of this research work is to determine the active didactic strategies applicable to promote reflective critical thinking in the students of the sixth semester of the PCEI career period April - September 2022. The methods used were of a mixed approach, that is, qualitative and quantitative, with which it was possible to obtain the necessary information to respond to the problem of the study. In the results obtained, the need to include much more active didactic strategies in the training of students was evidenced, such data were obtained through a survey generated with the Google forms tool. To conclude, the research work concludes that when students are interested in the mechanism provided by the teacher when teaching class content, there is a greater possibility of performance and development of knowledge, which is the objective of education for students. promote the development of reflective critical thinking.